2015
DOI: 10.5194/bg-12-269-2015
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variations in concentration and lability of dissolved organic carbon in Tokyo Bay

Abstract: Abstract. Concentrations of recalcitrant and bioavailable dissolved organic carbon (DOC) and their seasonal variations were investigated at three stations in Tokyo Bay, Japan, and in two freshwater sources flowing into the bay. On average, recalcitrant DOC (RDOC), as a remnant of DOC after 150 days of bottle incubation, accounted for 78% of the total DOC in Shibaura sewage treatment plant (STP) effluent, 67% in the upper Arakawa River water, 66% in the lower Arakawa River water, and 78% in surface bay water. B… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 51 publications
1
20
0
Order By: Relevance
“…Previous studies have also shown larger seasonal variations at F3 than at F6 in salinity, nutrients, and chlorophyll a concentrations (Matsumura et al 2001;Kanda et al 2008). This is consistent with the fact that F3 is located in the innermost region of the bay, which directly receives massive amounts of freshwater, nutrients and organic matter from the land (e.g., Ninomiya et al 1996;Kubo et al 2015). Accordingly, the innermost region is characterized by large seasonal variations, strong stratification, high primary production, and frequent occurrence of hypoxic/anoxic waters in the water column (Shibata and Aruga 1982).…”
Section: Results and Discussion 41 Temperature Salinity Do And Chsupporting
confidence: 76%
See 4 more Smart Citations
“…Previous studies have also shown larger seasonal variations at F3 than at F6 in salinity, nutrients, and chlorophyll a concentrations (Matsumura et al 2001;Kanda et al 2008). This is consistent with the fact that F3 is located in the innermost region of the bay, which directly receives massive amounts of freshwater, nutrients and organic matter from the land (e.g., Ninomiya et al 1996;Kubo et al 2015). Accordingly, the innermost region is characterized by large seasonal variations, strong stratification, high primary production, and frequent occurrence of hypoxic/anoxic waters in the water column (Shibata and Aruga 1982).…”
Section: Results and Discussion 41 Temperature Salinity Do And Chsupporting
confidence: 76%
“…Because of these biological impacts on CO 2 , observed range in DIC was 1.2 and 1.7 times larger than in TA at F3 and F6, respectively. Variations in DIC, TA and pCO 2 are larger at F3 in the innermost bay than F6 in the central bay reflecting larger freshwater inputs and higher productivity/remineralization in the former region (Matsumura et al 2001;Kanda et al 2008;Kubo et al 2015). Figure 6 shows seasonal variation in Ωar in Tokyo Bay.…”
Section: Ta Dic and Pcomentioning
confidence: 93%
See 3 more Smart Citations